Chromosome 15 Imprinting Disorders: Genetic Laboratory Methodology and Approaches - Butler, Merlin G.; Duis, Jessica (Frontiers in Pediatrics, 2020)
Chromosome 15 imprinting disorders include Prader-Willi (PWS) and Angelman (AS) syndromes, which are caused by absent expression from the paternal or maternal allele in the chromosome 15q11.2-q13 region, respectively. In addition, chromosome 15q duplication caused by the presence of at least one additional maternally derived copy of the 15q11.2-q13 region can lead to seizures, intellectual disability and neuropsychiatric concerns. We focus on PWS and AS in this article and expand the discussion of clinical care focusing on a standard-of-care for genetic testing to include high-resolution studies to more specifically characterize the molecular mechanisms of disease. The importance of early diagnosis is emphasized in both syndromes.Accurate molecular characterization is needed in an era of personalized medicine. We include a step-wise genetic testing flow chart for clinicians with patients presenting with features of PWS and/or AS.